2019
DOI: 10.1177/0300060519848916
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of aromatase cytochrome P450 enzyme is associated with prolactinoma invasiveness in post-menopausal women

Abstract: Objectives To investigate the expression levels of aromatase cytochrome P450 enzyme (P450AROM) and related molecules—estrogen receptor-beta (ER-β), Ki-67, and p53—in prolactinoma tumor tissue from pre- and post-menopausal women, and to determine the associations of tumor invasiveness with expression levels of these genes. Methods This study recruited 90 patients with prolactinoma who underwent adenoidectomy between 2012 and 2017. Information was collected regarding clinical characteristics, hormones, laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…This study used rabbit monoclonal antibody clone EPR3778 which is a synthetic peptide corresponding to residues on the C-terminus of ER-β. The same antibody was used by other studies 23 - 25 and showed positive, specific staining for ERβ.…”
Section: Discussionmentioning
confidence: 95%
“…This study used rabbit monoclonal antibody clone EPR3778 which is a synthetic peptide corresponding to residues on the C-terminus of ER-β. The same antibody was used by other studies 23 - 25 and showed positive, specific staining for ERβ.…”
Section: Discussionmentioning
confidence: 95%
“…Increased aromatase expression (which catalyzes synthesis of estrogen from testosterone) was revealed in invasive prolactinomas in post-menopausal women, in comparison to its expression in noninvasive prolactinomas [28]. ER-β level was also significantly higher in patients resistant to bromocriptine [28].…”
Section: Molecular Pathogenesis Of Prolactinomas Important To Design Future Treatments Estrogenmentioning
confidence: 99%
“…Increased aromatase expression (which catalyzes synthesis of estrogen from testosterone) was revealed in invasive prolactinomas in post-menopausal women, in comparison to its expression in noninvasive prolactinomas [28]. ER-β level was also significantly higher in patients resistant to bromocriptine [28]. For medically refractory prolactinomas, lowering endogenous estrogen with aromatase inhibitors or employment of selective estrogen receptor modulators (SERMs) are treatment candidates [6].…”
Section: Molecular Pathogenesis Of Prolactinomas Important To Design Future Treatments Estrogenmentioning
confidence: 99%
“…Studies of aromatase overexpression and knockout transgenic mice models confirmed that estradiol is largely responsible for the maintenance of the population of lactotropic cells in males [32,33], apart from playing an essential role in the hypothalamus-pituitary regulation of testicular and associated functions [18,34]. With regard to aromatase expression in pituitary adenomas and its possible association with tumor subtype, sex and/or tumor size, the results are still confounding [29,[35][36][37] and await further multimethodological confirmation and testing. Of note, clinical management of hypogonadism in men with macroprolactinoma, which was refractive to dopamine agonists, required aromatase inhibitor treatment in addition to testosterone replacement, to prevent the secondary rise in PRL and, finally, the potential for tumor enlargement [38].…”
Section: Estrogen Signaling In the Anterior Pituitary And Prolactinommentioning
confidence: 99%
“…Su et al [37] analyzed the expression pattern of tumor stem-like cells isolated from MMQ rat prolactinoma cells and found that Bcl 2, VegfA, Pten, Jun, Fos, and Apc2 gene expressions were upregulated and the expression of Myc was downregulated in these cells. The model of cancer stem cell proposes that a small population of cells with stem-like properties initiates and maintains tumorigenesis and may be more resistant to therapy than other tumor cells [100,101].…”
Section: Effects Of Estradiol On Stem/progenitor Cells and Transdiffementioning
confidence: 99%